2004
DOI: 10.1074/jbc.m400965200
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of NafY (Apodinitrogenase γ Subunit) from Azotobacter vinelandii

Abstract: The formation of an active dinitrogenase requires the synthesis and the insertion of the iron-molybdenum cofactor (FeMo-co) into a presynthesized apodinitrogenase. In Azotobacter vinelandii, NafY (also known as ␥ protein) has been proposed to be a FeMo-co insertase because of its ability to bind FeMo-co and apodinitrogenase. Here we report the purification and biochemical characterization of NafY and reach the following conclusions. First, NafY is a 26-kDa monomeric protein that binds one molecule of FeMo-co w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Additionally, NafY could prevent insertion of clusters different from FeMo-co, such as NifB-co or other biosynthetic intermediates, into the apo-NifDK active site. Consistent with this, NafY exhibits much higher affinity for FeMo-co (K D ϭ 60 nM) than NifB-co (K D in the low micromolar range) (11).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Additionally, NafY could prevent insertion of clusters different from FeMo-co, such as NifB-co or other biosynthetic intermediates, into the apo-NifDK active site. Consistent with this, NafY exhibits much higher affinity for FeMo-co (K D ϭ 60 nM) than NifB-co (K D in the low micromolar range) (11).…”
Section: Discussionsupporting
confidence: 61%
“…through contacts that include a surface-exposed histidine residue (11). X-ray crystallography showed that core-NafY has a different structure than the FeMo-co-binding region of NifDK, precluding the identification of a FeMo-co-binding region in NafY based on structural similarity (12).…”
mentioning
confidence: 99%
“…Two roles for NafY have been proposed: (a) stabilization of P-clustercontaining apo-NifDK protein in a conformation amenable to FeMo-co insertion, and (b) insertion of FeMo-co into apo-NifDK (33, 69). Consistently, purified NafY protein binds tightly either apo-NifDK or FeMo-co (70). NafY is a 26-kDa monomeric protein composed of two domains that can be separately expressed and purified.…”
Section: The Metallocluster Carrier Proteins Nifx and Nafymentioning
confidence: 97%
“…The three-dimensional structure of the FeMo-co binding domain of NafY has been solved and folds differently than the FeMo-co binding site in NifDK (20) (Figure 8). Site-directed mutagenesis studies on NafY suggested the His 121 residue as a likely ligand to FeMo-co (70). This residue is part of a His-Phe-Gly sequence conserved in NifX, NifB, and VnfX, all of which bind either NifBco or FeMo-co.…”
Section: The Metallocluster Carrier Proteins Nifx and Nafymentioning
confidence: 99%
“…Its 14 kDa C-terminal domain binds FeMo-co without the participation of any intermediates and promotes its insertion into apo-NifDK. In particular, mutational analysis indicated that a conserved His 121 of NafY is directly involved in FeMo-co binding (78).…”
Section: Metallocluster Carrier Proteins: Nifx and Nafymentioning
confidence: 99%